Experimental investigation of the vertical shear performance of steel–concrete composite girders under negative moment. (1st February 2021) - Zhou, Xuhong; Men, Pengfei; Di, Jin; Qin, Fengjiang
Highlights: Vertical shear behaviour of steel–concrete composite girders under negative moment. Non-compact sections are considered. A nonlinear finite element model was developed and verified using tests results. The shear distribution of the cross-section in the load process was investigated. Concrete slab contributes greatly to the shear capacity of non-compact girders. Abstract: To investigate the vertical shear performance of steel–concrete composite girders commonly used in bridge engineering, experimental tests were conducted on five simply supported composite girders and one bare steel girder under negative moments. The main test parameters were depth and reinforcement ratio of concrete slab, connection type, and web thickness. The test results showed that the ultimate load of the composite girder increased by 10–20% compared with that of the bare steel girder. When the concrete slab thickness increased from 115 mm to 180 mm, the reinforcement ratio was doubled, web thickness increased from 6 mm to 8 mm, the shear capacity of the composite girders increased by 9.1%, 4.4%, and 49%, respectively. The specimen with Perfobond rib connectors exhibited comparatively better ductility. Compared with the results obtained with the current AASHTO and EC4 codes, the shear capacity increased by 8–16% and 5.8% for composite girders with web thicknesses of 6 mm and 8 mm, respectively. A nonlinear finite element model was developed and verified using the test results. Using the validated numerical model, the shear distribution of the cross-section was investigated and parametric analyses were conducted. The shear distribution of the section was divided into four stages, namely elastic, slab cracking, steady, and web buckling stages, during the entire loading procedure. Parameter analysis showed that the slab thickness significantly influences the shear capacity of the composite girder. With increasing web depth–thickness ratio, the contribution of the concrete slab to the shear capacity increases.